Effect of culture media and auxin on growth and betalain accumulation in the hairy root cultures of red chard (Beta vulgaris L. var. cicla) - Moon, Sua; Seo, Hyewon; Lee, Minhwan; Uddin, Md Romij; Sathasivam, Ramaraj; Park, Chanung; Lee, Moon-Sub; Shin, Su Young; Park, Sang Un (Journal of Phytology, 2025)
This study analyzes the response of biomass production and betalain biosynthesis in hairy root cultures of red Swiss chard (Beta vulgaris L. var. cicla). Among the media tested, half-strength Schenk and Hildebrandt (1/2 SH) medium yielded the highest dry weight (413.3±42 mg/flask DW), whereas full SH medium appeared to be more consistent (390.0±10 mg/flask DW). Similar trends were observed in B5 and Murashige and Skoog (MS) media, where halving nutrient concentrations had minimal impact on biomass yield but significantly enhanced betalain accumulation. In addition, in this study, we further assessed the influence of different concentrations and various types of auxins on root and metabolite production. The result showed that 0.1 mg/L naphthalene acetic acid (NAA) was the optimum concentration for biomass production (443.3±12 mg/flask DW), while 0.5 mg/L indole-3-acetic acid (IAA) was the best for the production of betacyanin (3.028 mg/g), betaxanthin (1.938 mg/g DW), and total betalain content (4.966 mg/g DW). The findings highlight that reduced nutrient concentrations, particularly in SH medium, and precise auxin optimization can enhance both biomass and betalin production. These results provide valuable insights into optimizing hairy root culture systems for commercial applications in enhancing the secondary metabolite production in B. vulgaris.